Sharing the Burden: Climate responsibility beyond the nation-state - Fryett, Oliver (Consilience, 2022)
Crafting an adequate and cohesive global response to climate change has presented a monumental challenge. Fairly distributing climate responsibility, the concept of common but differentiated responsibilities for climate action, has been a key obstacle. Traditionally, climate responsibility has focused on the nation-state, yet these methods of responsibility allocation have failed in their key goal; to drive effective action to respond to the social and environmental consequences of climate change. This paper seeks to strengthen the link between climate responsibility and effective action across society. Building on currently accepted methods of responsibility allocation, particularly the ‘Carbon Majors’, I map the transfer of wealth during the production of greenhouse gases from extraction location to end recipient in company shareholders, with the aim of better representing a problem that is not neatly contained within national borders.